(untitled) - Price, John Ellis (New York, 2011)
Content shows you how to use QuickBooks 2011 software with selected end-of-chapter problems and mini practice sets from College accounting, 13e. The transactions and instructions for each problem and mini-practice sets are included in the Student Guide for Quickbooks 2011.
Keywords: Small business,Doanh nghiệp nhỏ; Computer programs,Accounting,Chương trình máy tính,Kế toán